The Evaluation model of entrepreneurial preparedness for the female population at social risk linked to human mobility processes in Guayaquil - García Coronel, Mariella Zoila; Dazza Delgado, Angela Maria; Samaniego Orrala, Jorge Andrés (Revista Internacional de Estudios en Ciencias Administrativas STRATEGOS, 2026)
Female entrepreneurship has become an increasingly relevant strategy for promoting social inclusion and economic strengthening among populations exposed to vulnerability and human mobility processes in Latin America. However, many institutional interventions continue to implement self-employment programs without previously identifying whether beneficiaries possess the necessary conditions to sustain entrepreneurial initiatives. In response to this gap, this study aimed to design and apply an Evaluation Model of Entrepreneurial Preparedness (MEPRE-EM) for the female population at social risk linked to human mobility processes in Guayaquil. The research adopted a quantitative approach with a non-experimental and descriptive-propositional design. Data were collected through a Likert-scale questionnaire administered to 236 women registered in a foundation dedicated to entrepreneurial training. The instrument included 30 items grouped into ten dimensions and demonstrated high internal consistency (Cronbach’s alpha = 0.853). Descriptive statistics and dimensional standardization procedures were used to construct the preparedness index. The results revealed an overall MEPRE-EM score of 66.74 out of 100, placing participants within a favorable level of entrepreneurial preparedness. The highest scores were observed in human capital and economic autonomy, while economic vulnerability, resilience, and innovation showed comparatively lower performance. The findings suggest that prior diagnostic evaluation may contribute to improving institutional decision-making, optimizing resource allocation, and designing differentiated intervention pathways before implementing self-employment programs for vulnerable women.
Keywords: Evaluation model; entrepreneurial; female population; social risk linked